1990
DOI: 10.1002/jmr.300030105
|View full text |Cite
|
Sign up to set email alerts
|

The formation of mispairs by 8‐oxyguanine as a pathway of mutations induced by irradiation and oxygen radicals

Abstract: Guanine conversion to 8-oxyguanine (OG) was induced by irradiation and oxygen radicals. The pathways of mutations caused by such DNA damage have been considered. Minima of interaction energies of OG with nucleic acid bases are revealed via classical potential function calculations. The minima exist for OG*:G and OG*:A base pairs, with syn-conformation of OG* and OG:T wobble base pairs. The mutual positions of glycosyl bonds in these base pairs are quite close to those for Watson-Crick pairs, and energies of OG… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

1998
1998
2013
2013

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 18 publications
0
11
0
Order By: Relevance
“…1B, the L-oriented construct measures the sum of (T⅐G) lagging ϩ (A⅐C) leading , whereas the R-oriented construct measures (T⅐G) leading ϩ (A⅐C) lagging . Given that T⅐G mispairs are generally much more frequent than A⅐C mispairs (30)(31)(32)(33)(34)(35)(36)(37), the L orientation measures (T⅐G) lagging , and the R orientation measures (T⅐G) leading . Our observation that the R orientation is more mutable than the L orientation (Tables 2 and 3) thus indicates that the leading strand produces more T⅐G errors and therefore that lagging strand replication is the more accurate one.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…1B, the L-oriented construct measures the sum of (T⅐G) lagging ϩ (A⅐C) leading , whereas the R-oriented construct measures (T⅐G) leading ϩ (A⅐C) lagging . Given that T⅐G mispairs are generally much more frequent than A⅐C mispairs (30)(31)(32)(33)(34)(35)(36)(37), the L orientation measures (T⅐G) lagging , and the R orientation measures (T⅐G) leading . Our observation that the R orientation is more mutable than the L orientation (Tables 2 and 3) thus indicates that the leading strand produces more T⅐G errors and therefore that lagging strand replication is the more accurate one.…”
Section: Discussionmentioning
confidence: 99%
“…In deciding which mispair may be predominantly responsible for each base pair substitution, we surveyed the literature for direct measurements of misinsertion frequencies as well as the relative efficiencies by which the various mispairs can be extended by DNA polymerases (30)(31)(32)(33)(34)(35)(36)(37). The latter aspect is important because reduced extension efficiency correlates with increased removal by exonucleolytic proofreading (e.g., see ref.…”
Section: Discussionmentioning
confidence: 99%
“…In 1980's it was shown that the physical properties, conformations and the biological functions in many respects are determined by the non-bonded interactions [109]. The non-bonded interactions were calculated using atom-atom potential functions having the form:…”
Section: Insert Figure 1 Herementioning
confidence: 99%
“…The atomic charges used in formulas (2) and (3) were obtained by quantum chemistry methods. The effective charges on atoms the authors [109,110] have received by summation of the π-electron charges, determined by the Hückel method [110], and σ-electron charges, calculated with help of parameter suggested by Berthod and Pullman [111]. By using these new non-bonded atom-atom potentials for calculating the non-bonded interactions, important and new results were obtained.…”
Section: Insert Figure 1 Herementioning
confidence: 99%
See 1 more Smart Citation